Collaborative approach to foreign policy : CARICOM and the Regional Negotiating Mechanism (RNM) - Mohammed, Debbie Ann (2003)
Focuses on those aspects of CARICOM's foreign policy agenda with specific reference to the role of and challenges to the Regional Negotiating Mechanism (RNM) in trade negotiations